S‐Nitrosated alpha‐1‐acid glycoprotein exhibits antibacterial activity against multidrug‐resistant bacteria strains and synergistically enhances the effect of antibiotics. Issue 3 (4th February 2019) - Ishima, Yu; Watanabe, Kaori; Chuang, Victor T. G.; Takeda, Iyo; Kuroda, Teruo; Ogawa, Wakano; Watanabe, Hiroshi; Iwao, Yasunori; Ishida, Tatsuhiro; Otagiri, Masaki; Maruyama, Toru
Abstract: Alpha‐1‐acid glycoprotein (AGP) is a major acute‐phase protein. Biosynthesis of AGP increases markedly during inflammation and infection, similar to nitric oxide (NO) biosynthesis. AGP variant A (AGP) contains a reduced cysteine (Cys149). Previously, we reported that S ‐nitrosated AGP (SNO‐AGP) synthesized by reaction with a NO donor, possessed very strong broad‐spectrum antimicrobial activity (IC50 = 10 −9 ‐10 −6 M). In this study, using a cecal ligation and puncture animal model, we confirmed that AGP can be endogenously S ‐nitrosated during infection. Furthermore, we examined the antibacterial property of SNO‐AGP against multidrug‐resistant Klebsiella pneumoniae and Pseudomonas aeruginosa to investigate the involvement of SNO‐AGP in the host defense system. Our results showed that SNO‐AGP could inhibit multidrug efflux pump, AcrAB‐TolC, a major contributor to bacterial multidrug resistance. In addition, SNO‐AGP decreased biofilm formation and ATP level in bacteria, indicating that SNO‐AGP can revert drug resistance. It was also noteworthy that SNO‐AGP showed synergistic effects with the existing antibiotics (oxacillin, imipenem, norfloxacin, erythromycin, and tetracycline). In conclusion, SNO‐AGP participated in the host defense system and has potential as a novel agent for single or combination antimicrobial therapy.